2015
DOI: 10.1186/s12889-015-1835-x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive health literacy in Japan is lower than in Europe: a validated Japanese-language assessment of health literacy

Abstract: BackgroundHealth literacy, or the ability to access, understand, appraise and apply health information, is central to individuals’ health and well-being. A comprehensive, concept-based measure of most dimensions of health literacy has been developed for the general population in Europe, which enables comparisons within and between countries. This study seeks to validate this tool for use in Japan, and to use a Japanese translation to compare health literacy levels in Japan and Europe.MethodsA total of 1054 Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
217
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 254 publications
(278 citation statements)
references
References 15 publications
32
217
4
3
Order By: Relevance
“…(, ) and Nakayama et al. (), we found that a 12‐dimensional model, reflecting the hypothesis of the four cognitive domains being integrated in the three health domains, fit the data better than the 1‐ and 3‐dimensional models. Despite the theoretically funded 12‐dimensional structure described in the conceptual framework (HLS‐EU Consortium, ) and the absence of empirical evidence supporting a unidimensional scale, researchers continually add up the scores to one general index (e.g., Palumbo et al., ; Sørensen et al., , ; Toçi, Burazeri, Sørensen, Kamberi, & Brand, ).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…(, ) and Nakayama et al. (), we found that a 12‐dimensional model, reflecting the hypothesis of the four cognitive domains being integrated in the three health domains, fit the data better than the 1‐ and 3‐dimensional models. Despite the theoretically funded 12‐dimensional structure described in the conceptual framework (HLS‐EU Consortium, ) and the absence of empirical evidence supporting a unidimensional scale, researchers continually add up the scores to one general index (e.g., Palumbo et al., ; Sørensen et al., , ; Toçi, Burazeri, Sørensen, Kamberi, & Brand, ).…”
Section: Discussionsupporting
confidence: 46%
“…This article seeks to evaluate the plausibility of the interpretations and uses of the European Health Literacy Survey Questionnaire (HLS‐EU‐Q47) sum score found in peer‐reviewed publications (Nakayama et al., ; Palumbo, Annarumma, Adinolfi, Musella, & Piscopo, ; Sørensen et al., , ). More specifically, we aim to evaluate the plausibility of the claims, assumptions and inferences that have been made based on the HLS‐EU‐Q47 score(s) because these might influence health policies.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, similar results are obtained from studies reporting health literacy and self-rated health [30]. According to the WHO [33], to reach a state of complete physical, mental and social well-being, an individual or group must be able to identify and realize aspirations, satisfy needs, and change or cope with the environment.…”
Section: Discussionmentioning
confidence: 58%
“…HL-SDHQ referred the definition of health literacy for the domain of health promotion; we, therefore, used the HP-HL index of the Japanese version of the HLS-EU-Q47 [30] to confirm scale validity. We expected it to better recognize health literacy which needs to realize health promotion than HP-HL index because HL-SDHQ clearly focuses on the social determinants of health.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that Japanese people had more difficulty in obtaining reliable and understandable health information compared to those in European countries, partly because of the absence of a reliable and comprehensive health information website comparable to MedlinePlus (US National Library of Medicine). 28 Health literacy is determined by the interaction of individual skills and abilities with the demands of society and the contexts within which people act. 4 Developing a reliable portal site of health information for general public may reduce the difference in the utilization of health information on the Internet by level of health literacy.…”
Section: Discussionmentioning
confidence: 99%